Multitemporalidad de la variabilidad climática en diferentes áreas protegidas del departamento de Loreto, Perú, 2022 - Espin Navarrete, Michelle Belén (2024)
Protected areas may be the most sensitive areas of the planet to climate change; being fragments amid degraded landscapes, they harbor species with limiting environmental tolerance. This research aimed to analyze the temporality of climatic variability in natural protected areas in the Department of Loreto to indicate anomalies related to climatic normal, trends, and correlation of mean temperature and precipitation in these places of relevance for conservation. Data from the ERA5-LAND reanalysis were used to obtain complete historical records for application in the context of climate change. Mann-Kendall, Sen's slope estimator and innovative trend analysis were used to identify the trend. To investigate the relationship between climatic variables, Spearman's correlation was applied. The analysis showed that average temperature and precipitation anomalies are discontinuous but more frequent. There is a trend of progressive temperature increase and a generalized decrease in precipitation. In addition, the correlation between climatic variables is inverse in all cases. Güeppí Sekime National Park presented less climatic variability in temperature and precipitation, while Matsés National Reserve was more affected in both aspects.